Dissecting the Tectal Output Channels for Orienting and Defense Responses - Isa, Kaoru (eNeuro, 2020)
Electrical stimulation and lesion experiments in 1980’s suggested that the crossed descending pathway from the deeper layers of superior colliculus (SCd) controls orienting responses, while the uncrossed pathway mediates defense-like behavior. To overcome the limitation of these classical studies and explicitly dissect the structure and function of these two pathways, we performed selective optogenetic activation of each pathway in male mice with channelrhodopsin 2 (ChR2) expression by Cre driver using double viral vector techniques. Brief photostimulation of the crossed pathway evoked short latency contraversive orienting-like head turns, while extended stimulation induced body turn responses. In contrast, stimulation of the uncrossed pathway induced short-latency upward head movements followed by longer-latency defense-like behaviors including retreat and flight. The novel discovery was that while the evoked orienting responses were stereotyped, the defense-like responses varied considerably depending on the environment, suggesting that uncrossed output can be influenced by top-down modification of the SC or its target areas. This further suggests that the connection of the SCd-defense system with non-motor, affective and cognitive structures. Tracing the whole axonal trajectories of these two pathways revealed existence of both ascending and descending branches targeting different areas in the thalamus, midbrain, pons, medulla, and/or spinal cord, including projections which could not be detected in the classical studies; the crossed pathway has some ipsilaterally descending collaterals and the uncrossed pathway has some contralaterally descending collaterals. Some of the connections might explain the context-dependent modulation of the defense-like responses. Thus, the classical views on the tectal output systems are updated.